(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
Hydrolysis of the lignocellulosic biomass results in the release of high-value chemicals that during industrial processing can be recovered with membrane technologies. To maintain an effective performance of the membranes used in the technological processing of biomass, their regular cleaning is essential. Although several guidelines may be found for membrane cleaning in the cases of organic fouling, the data for cleaning membranes fouled by hydrolyzed lignocellulosic biomass is limited. Current research is aimed to evaluate physical (air backpulse) and common cheap chemical membrane cleaning methods. The results showed that air backpulse alone had a minor (9%) effect on the membrane cleaning. The alternation of NaOH (1 %) solution with the NaClO (200 mg/L of Free chlorine) was the most effective approach for membrane cleaning. The cleaning effectiveness was 95.1 % for 50 nm membrane and 89 % for 200 nm membrane, indicating that membranes used for hydrolyzed lignocellulosic biomass filtration can be effectively cleaned using affordable and accessible chemicals.